Essentials and assessment of risk management - Grima, Simion; Torre-Enciso, Isabel Martínez; Castelli, Maurizioa (Emerald Publishing Limited, 2025)
The need to manage risk is increasingly featured in legislation and regulations. Simultaneously the need to integrate risk management into general management practices of organisations is fast becoming a key objective for all stakeholders. In addition, the drive to improve corporate governance is compelling organisations to examine the manner in which they manage risks and operational and strategic levels. The first volume of The FERMA-rimap Series describes the principles of risk and enterprise risk management (ERM) as well as the aims and benefits of an effective enterprise risk management. All risk professionals have a duty to remain updated with the evolution of the risk landscape. The FERMA-rimap Series serves as a proactive, continuous and dynamic learning and research platform to respond to risk managers' present and future educational and professional needs. The volumes set a crucial standard taxonomy for European Risk Professionals and an essential reading for students aspiring to gain a qualification in Risk Management.
Includes index.
Keywords: Risk management.; Business & Economics -- Finance -- Financial Risk Management.; Risk assessment.; Finance and the finance industry.; elektronické knihy; electronic books